Cronyism, Oligarchy and Governance in the Philippines: 1970s vs. 2020s - Bulaong, Oscar, Jr (Archīum Ateneo, 2022)
Martial Law exacerbated cronyism and oligarchy by concentrating political power into the hands of one political clan. Technocratic industrial policy combined with political anti-oligarch rhetoric spurred the rationalization and liberalization of different economic sectors. Some traditional business oligarchs were quickly displaced by a new cohort of business leaders with strong ties to the Marcos administration. This was the basic recipe for malgovernance and one of the deepest economic implosions faced by the Philippines in the early-1980s that eventually led to the dictator’s removal via the 1986 EDSA revolution. While institutional reforms and subsequent economic recovery has been achieved by post-EDSA Presidents, economic and political governance challenges persist as the risks of cronyism and oligarchy only evolve over time. Reformists appear to have liberalized the economy and spurred economic growth, but they have made little progress to liberalize the political system. The tendency for political clans to concentrate power remains. This underpins the reform agenda to continue to rebalance economic and political power in favor of stronger inclusion and competition, in turn supporting inclusive development.